Paranasal sinus metastasis of breast cancer. (27th June 2014) - Pittoni, P; Di Lascio, S; Conti-Beltraminelli, M; Valli, MC; Espeli, V; Bongiovanni, M; Richetti, A; Pagani, O
Abstract : A 76-year-old woman presented with symptoms suggestive of acute sinusitis. Previously, her breast carcinoma was treated with right lumpectomy, adjuvant chemotherapy and breast radiotherapy. She remained free from recurrence for the following 8 years. After initial treatment with antibiotics, the local symptom worsened with exophthalmos, eye blindness and development of an ulceration of the hard palate. MRI showed irregular enhancement of the nasal cavity extended to the maxillary sinus and ethmoidal lamina and concomitant infiltration of the orbit and skull base. A biopsy of the palatal ulcer showed a poorly differentiated adenocarcinoma and was compared with the histology of the primary breast tumour and it was concluded for the same morphology. After discussion at the multidisciplinary team, a specific chemotherapy has been activated with an initial local response. Further surgical resection was not thought appropriate and the patient has subsequently undergone palliative radiotherapy to the right paranasal lesions to improve local disease control.